2020
DOI: 10.1515/nanoph-2020-0343
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-plane investigation of plasmonic bound states in the continuum and molecular emission coupling

Abstract: Bound states in the continuum (BICs) or trapped modes can provide an important new avenue for strong light confinement via destructive interference. Dielectric photonic structures have been extensively studied for optical BICs. However, BICs in plasmonic nanostructures have not been explored much yet. Herein, we present a thorough experimental study of plasmonic BICs via Fourier-plane spectroscopy and imaging. Optical mode dispersion in a metal grating covered by a dielectric layer is directly measured in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Following Ref. [23], we consider the case when two optical resonances are coupled to the same radiation channel; the optical interaction between them is described by the non-Hermitian Hamiltonian without taking into account the nonradiative damping terms [8,13]:…”
Section: Friedrich-wintgen Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Ref. [23], we consider the case when two optical resonances are coupled to the same radiation channel; the optical interaction between them is described by the non-Hermitian Hamiltonian without taking into account the nonradiative damping terms [8,13]:…”
Section: Friedrich-wintgen Modelmentioning
confidence: 99%
“…In this work, we will be interested in the third type of quasi-BIC. This type of quasi-BIC occurs when two non-orthogonal modes are coupled to the same radiation channel and a strong-coupling regime of avoided crossing arises with appropriate conditions in parametric space [10,12,[20][21][22][23]. This regime is described by the Friedrich-Wintgen model [24] when due to destructive interference one of the emitting modes disappears and the other becomes more lossy due to constructive interference.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many strategies have been proposed to achieve extremely sharp plasmon resonances by mitigating their internal or/and radiative losses. [ 12–39 ] For instance, utilizing alternative plasmonic materials [ 12,13 ] or gain materials [ 14,15 ] have been demonstrated as an effective method to suppress the nonradiative losses. More efforts have been made to suppress the radiative damping by creating various unconventional plasmon resonances, such as Fano resonances, [ 16–19 ] surface lattice resonances (SLRs), [ 20–27 ] quasi‐bound states in the continuum (quasi‐BIC), [ 28–32 ] and Tamm plasmon resonances.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–39 ] For instance, utilizing alternative plasmonic materials [ 12,13 ] or gain materials [ 14,15 ] have been demonstrated as an effective method to suppress the nonradiative losses. More efforts have been made to suppress the radiative damping by creating various unconventional plasmon resonances, such as Fano resonances, [ 16–19 ] surface lattice resonances (SLRs), [ 20–27 ] quasi‐bound states in the continuum (quasi‐BIC), [ 28–32 ] and Tamm plasmon resonances. [ 33,34 ] These hybrid modes are usually achieved by the destructive interference between two radiation channels or coupling the plasmon resonances with a high radiative loss to the other types of resonances with a low radiative loss.…”
Section: Introductionmentioning
confidence: 99%
“…Q ‐factor and threshold gain have major influences on the parameter β of a laser. Studies have demonstrated laser applications of BICs through dark resonance of 2D periodic array nanostructures; [ 35,41–45 ] however, most of these studies have not strictly demonstrated a low‐threshold laser with a sufficiently high β value to achieve a Q ‐factor resonance as high as that of a BIC. Because BICs have no emission channels, their output power is usually low.…”
Section: Introductionmentioning
confidence: 99%